Tracking Hutan Manggrove Tracking Hutan Mangrove Di Pesisir Pantai Sulawesi Utara Berbasis Citra Satelit - Ayu Chantika Haribulan; Marson J Budiman (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
Technology that is increasingly developing and advanced can provide progress in various social,economic and technological aspects. Currently,related agencies such as the marine and forestry services,the enviromental service,arr still largely unaware off the exitence of mangrove forest in north sulawesi. North Sulawesi Province has 11.456 ha of mangrove forest spread over 13 cities and regencies with various conditions.The use off satellite imagery technology or remote sensing is a solution to find out the unknow location of mangrove forest in North Sulawesi using landsat mapbox imagery data. Therefor, the purpose of making this application is to facilitate the relevant agencies in finding the exitence of mangrove forest in North Sulawesi. Keywords: Application,Mangrove forest,Satellite image